PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY DAN TOTAL ASSET TURNOVER TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - R. SRI HANDAYANI; ELVIRA NANDA APRILIA (JURNAL AKUNTANSI DAN KEUANGAN, 2023)
This study aims to analyze the effect of current ratio, debt to equity ratio, return on equity, and total asset turnover on the return of shares of mining sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The population in this study is mining companies listed on the Indonesia Stock Exchange in 2018-2022. Research samples of 16 mining companies obtained by purposive sampling technique. Data analysis method with multiple linear regression. The results of this study show that partially the ROE variable has a positive effect and the TATO variable has a negative effect on stock returns, while the CR and DER variables have no effect. Simultaneously, the variables CR, DER, ROE, and TATO have no effect on stock returns.